Listening to the Centennial Consumer through Sensory Experience: The Professional Simulator as a Learning Tool for Experiential Marketing - Gotor Cuairán, Marta; Sutil Martín, Dolores Lucía; Sacristán Navarro, María Asunción (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This study, as suggested by the EEES, arises as a response to the need to strengthen the university´s link with the business world, using professional simulators based on experiential learning, which unifies methodologies and develops the skills that are required in real business scenarios in the area of Marketing and Advertising. Through laboratory dynamics, the students learned and applied consumer and preference research techniques in the field of sensory marketing, with an immersion connected between the university classroom and the business Atelier in the Spanish dermo-cosmetic sector.